Pengaruh Konflik Kerja, Beban Kerja dan Lingkungan Kerja Terhadap Turnover Karyawan ( Studi Pada Badan Kepegawaian dan Pengembangan dan Sumber Daya Manusia BKPSDM Kota Malang) - Titi Puspitasari; N Rachma; Mohammad Rizal (UNIVERSITAS ISLAM MALANG, 2022)
Abstract This study aims to see the effect of Work Conflict (X1), Workload (X2), and Work Environment (X3) on Turnover Intention (Y) of Employees at the Agency for Personnel and Human Resources Development (BKPSDM) City and Regency of Malang. Turnover intention is one of the symptoms that has recently been given more attention because this phenomenon often afflicts employees at the Agency for Personnel and Human Resources Development (BKPSDM), of course this phenomenon is often influenced by environmental factors such as work conflict, workload and work environment. This study uses quantitative research using data analysis tools, namely the SPSS version 16.0 application. The number of respondents used in this study was 131 samples. Researchers in determining the number of samples from the population in this study, namely by taking 10%-15% or 20%-25% of the total population. The data collection method in this study is a questionnaire and how to assess it using a Likert scale. The results of this study are that there is a significant effect of Work Conflict (X1), Workload (X2), and Work Environment (X3) on Employee Turnover Intention (Y) at the Agency for Personnel and Human Resources Development (BKPSDM) Keywords: Workload, Work Environment and Employee Turnover Intention.